Particulate emissions from turbulent diffusion flames with entrained droplets: A laboratory simulation of gas flaring emissions. (September 2021) - Kazemimanesh, Mohsen; Baldelli, Alberto; Trivanovic, Una; Popovicheva, Olga; Timofeev, Mikhail; Shonija, Natalia; Obvintsev, Yuri; Kuang, Chen; Jefferson, A. Melina; Corbin, Joel C.; Goss, Greg G.; Alessi, Daniel S.; et al.
Abstract: Global flaring volume exceeds 140 billion m 3 annually and flares are a key source of particulate air pollution. During flowback operations subsequent to fracturing of a well, droplets of flowback water—with varying levels of dissolved salts—can be entrained in the flared gas. Despite the widespread prevalence of fracturing, very little is known about the properties of particle emissions from such flares. To study these properties, we used a laboratory pipe flare producing a turbulent diffusion flame without and with entrained droplets. Entrained droplets of deionized water, sodium chloride solution, and solutions representing two typical flowback waters in Canada (Cardium and Duvernay) were used. Three different gas compositions (consisting of C1 to C7 alkanes, carbon dioxide, and nitrogen) representative of flares in the upstream oil and gas sector in Alberta, Canada were studied. The results showed that the salt in the entrained flowback droplets increased the particle concentration by about one order of magnitude by forming freshly nucleated salt particles. Moreover, soot concentration increased as a result of entrained salt. Effective density results showed that small particles (<150 nm mobility diameter) were mainly salt, while large particles (>300 nm) were mostly soot—a result also confirmed by transmission electron microscopy (TEM). Electron micrographs showed that the majority of particles were either individual salt particles or internally-mixed soot-salt particles. The inorganic salt particles mainly consisted of Na and Cl, the two most abundant elements in flowback water. Raman spectroscopy indicated that the salt had much less (or no) impact on graphitic nanostructure of soot, while the fuel blend had a significant effect. The results of this study are significant as they reveal that current emission inventories based on flaring of gases only may underestimate soot emissions from flares with entrained droplets. Graphical abstract: Image 1 Highlights: Entrained flowback droplets increased soot concentration from flares. Total particle concentration increased by order of magnitude with entrained droplets. Most particles were internally-mixed soot-salt particles or isolated salt particles. Non-soot particles mainly consisted of sodium and chloride. Fuel blend and salt had significant and no impact on soot nanostructure, respectively.